Sebaran Nitrat dan Kelimpahan Fitoplankton di Pantai Tanah Merah dan Pulau Semujur - Muh. Yusuf; Aditya Pamungkas; Mu’alimah Hudatwi; Irvani (Universitas Hang Tuah, 2020)
The waters of Tanah Merah beach waters and Semujur Islands waters are both located in Bangka Tengah Regency. Geographically it can be indicated Tanah Merah is quite far from residential areas, while the other locations are in the inhabited small island waters (Semujur). These different geographical conditions can cause the content of nitrate nutrients to be different because the main source of nitrate nutrients comes from human activities. High nitrate nutrients will affect the abundance of phytoplankton in local waters. This study aims to determine the value and nitrate in relation to the abundance of phytoplankton in the sea. Moreover this research was applied in Tanah Merah beaches waters and Semujur Island waters, Bangka Tengah Regency, from February to April 2020. The results shown that the nitrate content in Tanah Merah beaches waters was 0.011-0.026 mg/LT (St.1-St.4) which was lower compared of 0.046-0.10 mg/L (St.9-St.12) at Semujur Island waters. Phytoplankton abundance data and Species Diversity Index (H ') show that the Tanah Merah beaches waters are 111,000-134,000 cells/L and the H' index is 2.06-2.16 lower than the phytoplankton abundance data in Semujur Island waters of 110,000 - 208,000 cells/L and the H 'index of 2.22-2.29. Others evident to support that data are the current velocity in Tanah Merah beaches waters ranges from 0.014-0.21 m/s less than Semujur Island waters at 0.22-0.32 m/s.